PEMANFAATAN POJOK LITERASI NUMERASI DI PANTI ASUHAN AISYIAH UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN PENGETAHUAN MATEMATIKA SANTRI - Sri Novia Martin; Widdya Rahmalina; Khairul Azmi; Asrina Mulyati; Siti Nur Hikmah; Meria Ultra Gusteti; Suci Wulandari (LPPM Universitas Abdurrab, 2023)
This study aims to increase the learning motivation and mathematical knowledge of students at the Aisyiah Orphanage through the creation of a Numeracy Literacy Corner. The method used is demonstration and group discussion. The students' study room at the orphanage was transformed into a numeracy literacy corner decorated with math learning media. The activity was carried out on June 3 2022 and involved students and supervisors at the Aisyiah Orphanage as targets. After carrying out the activity, the questionnaires distributed showed a high level of student satisfaction with an average score of 4.15. Apart from that, the students and coaches also showed high enthusiasm for the arrival of the team and asked for further guidance to increase enthusiasm for learning mathematics. The results of this study indicate that the activity of making a Numeracy Literacy Corner is effective in increasing the learning motivation and mathematical knowledge of students at the Aisyiah Orphanage. The recommendation from this study is to continue further guidance to further encourage the enthusiasm and skills of learning mathematics for students at the Aisyiah Orphanage